Extensin, an underestimated key component of cell wall defence?. (16th March 2021) - Castilleux, Romain; Plancot, Barbara; Vicré, Maité; Nguema-Ona, Eric; Driouich, Azeddine
Abstract: Background: Extensins are plant cell wall hydroxyproline-rich glycoproteins known to be involved in cell wall reinforcement in higher plants, and in defence against pathogen attacks. The ability of extensins to form intra- and intermolecular cross-links is directly related to their role in cell wall reinforcement. Formation of such cross-links requires appropriate glycosylation and structural conformation of the glycoprotein. Scope: Although the role of cell wall components in plant defence has drawn increasing interest over recent years, relatively little focus has been dedicated to extensins. Nevertheless, new insights were recently provided regarding the structure and the role of extensins and their glycosylation in plant–microbe interactions, stimulating an interesting debate from fellow cell wall community experts. We have previously revealed a distinct distribution of extensin epitopes in Arabidopsis thaliana wild-type roots and in mutants impaired in extensin arabinosylation, in response to elicitation with flagellin 22. That study was recently debated in a Commentary by Tan and Mort (Tan L, Mort A. 2020. Extensins at the front line of plant defence. A commentary on: 'Extensin arabinosylation is involved in root response to elicitors and limits oomycete colonization'. Annals of Botany 125: vii–viii) and several points regarding our results were discussed. As a response, we herein clarify the points raised by Tan and Mort, and update the possible epitope structure recognized by the anti-extensin monoclonal antibodies. We also provide additional data showing differential distribution of LM1 extensin epitopes in roots between a mutant defective in PEROXIDASES 33 and 34 and the wild type, similarly to previous observations from the rra2 mutant defective in extensin arabinosylation. We propose these two peroxidases as potential candidates to specifically catalyse the cross-linking of extensins within the cell wall. Conclusions: Extensins play a major role within the cell wall to ensure root protection. The cross-linking of extensins, which requires correct glycosylation and specific peroxidases, is most likely to result in modulation of cell wall architecture that allows enhanced protection of root cells against invading pathogens. Study of the relationship between extensin glycosylation and their cross-linking is a very promising approach to further understand how the cell wall influences root immunity.